Performance improvement of torque characteristics using the Multi Type Interior Permanent Magnet motor - Norhisam, Misron, Prof. Madya Dr. (Praise Worthy Prize S.r.l., 2013)
Link to publisher's homepage at http://www.praiseworthyprize.com/